Web-Based Convection Service Information System Using Waterfall Method - Sunenti, Wawah Sri; Setiawan, Rony (CV.RIZANIA MEDIA PRATAMA, 2024)
Khandiq Convection is a garment business in Bandung that still uses manual methods for order processing and sales recording, leading to data inaccuracy and loss risks. As digital technology advances, many businesses have adopted web-based information systems to streamline operations. However, existing systems are often generic and not suited to the specific needs of small and medium enterprises (SMEs). This study aims to develop a web-based information system tailored to Khandiq Convection’s operations. Using the Waterfall method, the system was designed with CodeIgniter, PHP, and MySQL, and implemented via XAMPP. Data were collected through interviews, observation, and literature review. The results show that the system improves data accuracy, reduces errors, and enhances order and sales management. This solution addresses the gap in accessible and integrated digital tools for SME garment businesses, supporting operational efficiency and customer service in the digital era.